Nerve ultrasound findings differentiate Charcot-Marie-Tooth disease (CMT) 1A from other demyelinating CMTs. Issue 11 (November 2018) - Zanette, Giampietro; Fabrizi, Gian Maria; Taioli, Federica; Lauriola, Matteo Francesco; Badari, Andrea; Ferrarini, Moreno; Cavallaro, Tiziana; Tamburin, Stefano
Highlights: Nerve cross sectional area (CSA) is heterogenous across demyelinating CMTs. Average nerve CSA is significantly enlarged in CMT1A vs. other demyelinating CMTs. The large CSA spectrum in CMT1A may be related to its clinical variability. Abstract: Objective: Ulnar/median motor nerve conduction velocity (MNCV) is ≤38 m/s in demyelinating Charcot-Marie-Tooth disease (CMT). Previous nerve high resolution ultrasound (HRUS) studies explored demyelinating CMT assuming it as a homogeneous genetic/pathological entity or focused on CMT1A. Methods: To explore the spectrum of nerve HRUS findings in demyelinating CMTs, we recruited patients with CMT1A (N = 44), CMT1B (N = 9), CMTX (N = 8) and CMT4C (N = 4). They underwent nerve conduction study (NCS) and HRUS of the median, ulnar, peroneal nerve, and the brachial plexus. Results: Median, ulnar and peroneal MNCV significantly differed across CMT subtypes. Cross sectional area (CSA) was markedly and diffusely enlarged at all sites, except entrapment ones, in CMT1A, while it was slightly enlarged or within normal range in the other CMTs. No significant right-to-left difference was found. Age had limited effect on CSA. CSAs of some CMT1A patients largely overlapped with those of other demyelinating CMTs. A combination of three median CSA measures could separate CMT1A from other demyelinating CMTs. Conclusions: Nerve HRUS findings are heterogeneous in demyelinating CMTs. Significance: Nerve HRUS may separate CMT1A from other demyelinating CMTs. The large demyelinating CMTs HRUS spectrum may be related to its pathophysiological variability.